Perancangan Mesin Penggiling Jagung untuk Pakan Ternak - Ahmad Syahrizal Hamdani; Zetyawan Ardan; Muh. Maftuh; Krismon La Maru (Piston: Jurnal Teknologi, 2023)
The livestock sector is an important sector in the process of fulfilling food for the community. Livestock products are a source of animal protein, the demand for food from livestock in Indonesia continues to increase. Corn plants in Indonesia are very important as a source of carbohydrates and protein, corn is also in addition to being used as human food ingredients can also be used as animal feed, so the application of tools capable of producing animal feed is very necessary, especially those related to corn processing as fast and maximum animal feed with the aim of reducing damage and depreciation which is very closely related to the quality and quantity of feed products and the final result to be marketed. This corn grinding machine has two ways of operating, namely manually and mechanically. Mechanical milling technology, using a drive in the form of an electric motor (dynamo) or a self-driving motor in the form of a gasoline motor, and there is also using a crank as a drive (manual). In the process of grinding corn machine can produce 2kg = 3 minutes, in 1 hour 60 minutes. The capacity of the designed tool is 2 kg with a square-shaped grinding chamber, with a machine height of 92 cm, a frame height of 50 cm, and a frame width of 38 cm. In the process of grinding corn material, the difference in the initial weight of corn before grinding is 2 kg and after grinding is 1.96 kg for 3 minutes at 800 rpm or 40 kg/hour. The results of this design still need further development, in order to optimize its performance for corn grinders in the agricultural sector.